The Influence of Entrepreneurship Educational Characteristics on Traders' Income Levels and Business Development - Felia Siska; Sapriya; Nana Supriatna; Neiny Ratmaningsih; Irwan (Jurnal Iqra' : Kajian Ilmu Pendidikan, 2023)
This article aims to analyze the influence of entrepreneurship education characteristics on the level of income of traders and business development in the Minangkabau livestock market. The research method uses a quantitative approach with an SEM development model, using AMOS data processing. The research sample is a type A regional livestock market in West Sumatra. The results showed whether between entrepreneurship characteristics to the level of income of traders and business development in the Minangkabau livestock market: a). Entrepreneurship characteristics have a positive effect on the income level of traders, b). Entrepreneurship characteristics do not have a positive effect on business development, c). The income level of traders has a positive effect on business development, and d). The income level of traders has become an influential mediator in the relationship between service entrepreneurship characteristics and business development. Thus, entrepreneurship characteristics generally affect traders' income levels and business development in Minangkabau livestock markets. Keywords: Entrepreneurship Educational Characteristics, Income Level, Business Development